Sistemas Fiber-wireless 5G NR - Pereira, Luiz Augusto Melo (2020)
This work reports the design and implementation of an analog radio-over-???berbased fronthaul solution for 5G systems. We have numerically investigated the performance of orthogonal frequency division multiplexing (OFDM), generalized frequency division multiplexing(GFDM) and ???ltered OFDM (F-OFDM),which have beengenerated using Matlab integrated on Optisystem and demodulated in Matlab. Afterwards, we have reported a 5G FiWi system with Gbit/s throughput, using 5G newradio(5GNR)standard. Additionally, wehaveemployedtheBrazillian5Gtransceiver,whichcancoverOFDM,GFDMandF-OFDMwaveforms. Wehaveappliedthe Analog-radio-over-???ber (A-RoF) solution for simultaneously distribute multiple radiofrequency (RF) signals through optical fronthaul. Such solution take advantages of anInternetserviceproviderfordistributingRFsignalinthe5Gfrequencybands, e.g., 788MHz,3.5GHzand26GHz. Numericalandexperimentalresultsdemonstratedthe proposed solution feasibility, achieving throughput of 210.9 Mbit/s and 4.41 Gbit/s.